Liberalisation vs. governance : a discussion of racial politics in three literary works - Lam, David Ying Cai (2015)
This paper looks at three works – two Singaporean, one Malaysian – that lend themselves to the discussion on race; Scorpion Orchid by Lloyd Fernando, Malay Sketches by Alfian Sa’at, and Charged by Chong Tze Chian. This thesis will examine how the colonial legacy of racial sectarianism is carried into the present, and how it is perpetuated along the socioeconomic divide today through the three literary texts. The three texts reflect the detrimental effects that racial divides have on social cohesion, such as the escalation of racial conflict to feverish levels caused by racial segregation in Scorpion Orchid, the individual’s resentment towards other races through the institutionalisation of race in Charged, and the trap of false racial binaries across socioeconomic divides in Malay Sketches. The three novels paint the individual suffering that results from the over-politicisation and perpetuation of racial divides. Relationships and interpersonal communication breaks down when the “fail-safes” of censorship fall though, and the flaws of a socially-engineered and superficial social cohesiveness are revealed in the literary works.